Strong Damping‐Like Spin‐Orbit Torque and Tunable Dzyaloshinskii–Moriya Interaction Generated by Low‐Resistivity Pd1−xPtx Alloys. (27th February 2019) - Zhu, Lijun; Sobotkiewich, Kemal; Ma, Xin; Li, Xiaoqin; Ralph, Daniel C.; Buhrman, Robert A.
Abstract: Despite their great promise for providing a pathway for very efficient and fast manipulation of magnetization, spin‐orbit torque (SOT) operations are currently energy inefficient due to a low damping‐like SOT efficiency per unit current bias, and/or the very high resistivity of the spin Hall materials. This work reports an advantageous spin Hall material, Pd1− x Pt x, which combines a low resistivity with a giant spin Hall effect as evidenced with three independent SOT ferromagnetic detectors. The optimal Pd0.25 Pt0.75 alloy has a giant internal spin Hall ratio of >0.60 (damping‐like SOT efficiency of ≈0.26 for all three ferromagnets) and a low resistivity of ≈57.5 µΩ cm at a 4 nm thickness. Moreover, it is found that the Dzyaloshinskii–Moriya interaction (DMI), the key ingredient for the manipulation of chiral spin arrangements (e.g., magnetic skyrmions and chiral domain walls), is considerably strong at the Pd1− x Pt x /Fe0.6 Co0.2 B0.2 interface when compared to that at Ta/Fe0.6 Co0.2 B0.2 or W/Fe0.6 Co0.2 B0.2 interfaces and can be tuned by a factor of 5 through control of the interfacial spin‐orbital coupling via the heavy metal composition. This work establishes a very effective spin current generator that combines a notably high energy efficiency with a very strong and tunable DMI for advanced chiral spintronics and spin torque applications. Abstract : Spin‐orbit torque (SOT) operations are currently energy inefficient due to a low damping‐like SOT efficiency and/or the very high resistivity of the spin Hall materials. This work establishes a very effective spin current generator Pd1− x Pt x that combines a notably high energy efficiency with a very strong and tunable Dzyaloshinskii–Moriya interaction for advanced chiral spintronics and spin torque applications.